The Role of Nature in James Fenimore Cooper’s Novel “The Prairie”: An Ecocritical Study (Conference on English Language Teaching, 2025)
This study investigates the representation and significance of nature in James Fenimore Cooper's novel "The Prairie" through the lens of ecocriticism. Cooper’s narrative profoundly portrays the American wilderness, reflecting on humanity's complex relationship with the natural environment during the period of westward expansion. Employing an ecocritical framework, the analysis explores how Cooper delineates nature not merely as a backdrop but as an active, dynamic character that influences human actions and decisions. "The Prairie" vividly captures the grandeur and vastness of the American frontier, underscoring the simultaneous beauty and harshness of the natural world. Cooper uses detailed descriptions of landscapes and wildlife to illustrate nature’s autonomy, challenging the anthropocentric perspectives prevalent in early 19th-century American literature. The study further highlights the ecological consciousness present within the novel, revealing how Cooper anticipates contemporary environmental concerns by critiquing humanity's destructive exploitation of natural resources and disregard for ecological balance. Furthermore, this research emphasizes the role of the protagonist, Natty Bumppo, whose harmonious coexistence with nature provides a counter-narrative to exploitative attitudes. Bumppo embodies environmental ethics ahead of his time, advocating respect, stewardship, and coexistence. Ultimately, this ecocritical exploration of "The Prairie" demonstrates Cooper’s novel as an early literary call for environmental awareness, significantly contributing to discussions on the human-nature relationship. By reassessing Cooper’s ecological vision, the study underscores the continued relevance of his environmental perspectives and highlights literature’s enduring role in shaping ecological consciousness.